Pengaruh Lingkungan Kerja, Kepuasan Kerja, dan Disiplin Kerja Terhadap Produktivitas Karyawan (Studi Kasus PT. Easterntex Pandaan Jawa Timur) - Syahputra, Hafiz Firdaus; Sunaryo, Hadi; Khalikussabir, Khalikussabir (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This study analyzes the effect of work environment, job satisfaction, and work discipline on employee productivity at PT Easterntex Pandaan East Java. Using a quantitative method with a survey approach, data were collected through questionnaires distributed to 60 permanent employees in the mechanical division of PT Easterntex. Sample determination using non-probability sampling with saturated sample method. Data analysis techniques include descriptive analysis, validity testing, reliability, classical assumption test, multiple linear regression analysis, and hypothesis testing (t test and F test). The results showed that work environment, job satisfaction, and work discipline significantly affect employee productivity, both partially and simultaneously. A comfortable work environment, high levels of satisfaction, and good discipline are proven to encourage increased productivity. The implication of this finding emphasizes the importance of management's role in maintaining and improving these three aspects in order to achieve optimal productivity. Keywords: Work Environment, Job Satisfaction, Work Discipline, Employee Productivity.